Medical and legal significance of assessing the probability of brain death in patients after intraoperative cardiac arrest and successful cardiopulmonary resuscitation - V. L. Vinogradov; I. V. Pletyanova; K. K. Gubarev (Трансплантология (Москва), 2024)
Background. After successful cardiopulmonary resuscitation for intraoperative cardiac arrest, most patients die in the Intensive Care Unit from multiple organ failure, cardiovascular complications that develop after hypoxic-ischemic damage to the central nervous system. In some patients whose heart is still beating in conditions of mechanical ventilation, a complete and irreversible cessation of all brain functions may occur, that is, brain death.Objective. Based on clinical criteria, we made an attempt to assess the likelihood of developing a condition consistent with the diagnosis of brain death in those who sustained cardiac arrest during surgery or other medical manipulation and underwent successful cardiopulmonary resuscitation, but died later in the Intensive Care Unit.Material and methods. A retrospective analysis of medical records related to 45 clinical cases was performed to assess the likelihood of brain death according to the Quality Assurance Programme in the Deceased Donation Process (QAPDD) methodology, which has been used during an external audit in hospitals of Spain and specifically focused on the donation process after brain death.Results. In 30 (66.7%) patients, based on the proposed criteria, a high probability of developing brain death was noted. At the same time, in 27 (90%) cases, clinical signs of brain death were noted within the first 6 days after cardiopulmonary resuscitation. Biological death in these patients was ascertained within 1 to 119 days from the moment of the development of clinical signs of brain death.Inference. The concept of brain death has serious medical, economic, legal, and ethical implications. When clinical suspicion of brain death arises, it is important that all such undergo standard diagnostic procedures to objectively rule out or confirm the diagnosis of brain death.Conclusion. The probability brain death occurrence in patients after intraoperative cardiac arrest and successful cardiopulmonary resuscitation is statistically siqnificant at 66.7% (p=0.0196).